Perancangan Game Edukasi Berburu Suku Bauzi di Mambramo Papua - Agung Dwi Saputro (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2023)
The Bauzi is a tribe that inhabits the Mamberamo Raya district. The Bauzi  is classified as semi-nomadic who fully utilizes the existing ecosystems in their territory. The life of the Bauzi  belongs to the hunter-gatherer economy. They carry out hunting activities, fishing all year round, but there are some animals that are only available seasonally. Animals that can be hunted throughout the year are wild boar, while a some of bird species are only available in certain seasons. Currently, the media rarely discusses the Bauzi tribe. To more easily learn and get to know the Bauzi tribe, an educational game design for hunting the Bauzi  in Mambramo Raya can be made. The method used to design this game is the RAD (Rapid Application Development) method which is divided into three stages: planning, system design, and implementation. This Bauzi hunting educational game contains a pig hunting game and lessons about the Bauzi tribe, starting from the history of the Bauzi , their daily activities, how to hunt,  and tools used for hunting. The purpose of this game is to make it easier for people to learn about the Bauzi tribe with educational game media. The final result of this research is a desktop application that can be used as a learning medium for the Bauzi tribe in Mamberamo.